Small mammal populations of an agroecosystem in the Atlantic Forest domain, southeastern Brazil - DAndrea,PS. (2007)
This study reports 2 years of the population dynamics and reproduction of a small mammal community using the removal method. The study was conducted in a rural area of the Atlantic Forest, in Sumidouro, Rio de Janeiro State, Brazil. The population sizes, age structure and reproduction were studied for the four most common species in the study area. The overall diversity was 1.67 and ranged between 0.8 to 1.67. The species richness was 13 considering the whole study. The most abundant species were the rodents Nectomys squamipes (n = 133), Akodon cursor (n = 74), Oligoryzomys nigripes (n = 25) and the marsupials Didelphis aurita (n = 58) and Philander frenatus (n = 50). Seven other rodents were captured once: Necromys lasiurus, Akodon montensis, Sooretamys angouya, Oecomys catherine, Oxymycterus judex, Euryzygomatomys spinosus and Trinomys iheringi. There were higher peaks for diversity and species richness during the winter (dry) months, probably due to higher food availability. The marsupials had a seasonal reproduction with highest population sizes at the end of the rainy seasons. Nectomys squamipes reproduced mostly during rainy periods. Akodon cursor reproduced predominantly in the winter with the highest population peaks occurring during this season. The analysis of the population dynamics of the rodent species indicated that no species behaved as an agricultural pest, probably due to the heterogeneous landscape of high rotativity of vegetable cultivation. Rodent populations were more susceptible to the removal procedure than marsupial ones.